PRISMA Guidelines: Methodological Adaptation for Systematic Reviews in Education - Posso Pacheco, Richar Jacobo; Barba Miranda, Laura Cristina; Tenorio Sánchez, Raquel Arcenia; Caicedo-Quiroz, Rosangela; Maqueira-Caraballo, Giceya; Barzola-Monteses, Julio (Data and Metadata, 2025)
Introduction: Systematic reviews in education require methodological adaptations due to the complexity of educational data and contexts, making it necessary to adjust the PRISMA guidelines, initially designed for health, to meet the needs of the educational field. Objective: To adapt the PRISMA guidelines for their methodological implementation in systematic reviews within the educational domain. Methodos: A documentary and comparative analysis between PRISMA and educational studies was conducted, complemented by consultations with specialists, allowing the development of an adapted framework based on rigorous criteria and methodological tools tailored to education. Results: An adapted framework was proposed, including inclusion and exclusion criteria, methodological procedures, and tools for quality assessment, positively impacting the relevance, applicability, and rigor of educational systematic reviews. Conclusions: The adaptation of PRISMA to the educational field will enhance the quality of systematic reviews, strengthening their impact on policies, pedagogical strategies, and evidence-based teaching practices in complex contexts such as Latin America.